Effectiveness of Training Methods on Shot Put Athletic Learning Results - Juhanis; Sudirman; Hasyim; M. Said Zainuddin; Andi Muhammad Fadlih (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Athletics is the oldest sport or known as the Mother of Sport. The Mother of Sport is also called the mother of all sports. The reason athletics is called the Mother of Sport is because athletics is a combination consisting of walking, running, jumping and throwing.Athletic learning especially shot put at school, is increasingly in demand by students. This is due to the quality of the material provided by the teacher, this study aims to compare role-playing training methods of bullet repelling. The method used in this study is a 2x2 factorial experiment. The subject involved was students of athletic extracurricular members totaling 40 students. Data analysis in this study is two-way ANOVA using SPSS 20. The results of this study are 1) There is an effect of training methods on learning results of bullet repelling, 2) the effectiveness of learning outcomes is influenced by the quality of high arm muscle power, and not influenced by strength to the effectiveness of learning outcome to reject bullets. The conclusion can be adjusted to the characteristics of student learning.